2020
DOI: 10.3389/fphys.2020.00939
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics Associating With Circulating MicroRNA Profiles Reveal the Role of miR-383-5p in Rat Hippocampus Under Simulated Microgravity

Abstract: Microgravity impacts various aspects of human health. Yet the mechanisms of spaceflight-induced health problems are not elucidated. Here, we mapped the fusion systemic analysis of the serum metabolome and the circulating microRNAome in a hindlimb unloading rat model to simulate microgravity. The response of serum metabolites and microRNAs to simulated microgravity was striking. Integrated pathway analysis of altered serum metabolites and target genes of the significantly altered circulating miRNAs with Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Particularly, miR-383-5p was significantly increased, and aquaporin 4 (AQP4) decreased in the hippocampus. The authors suggest that bioinformatics could be used to map the crosstalk between the circulating metabolome and miRNAome to better to understand complex biological systems under µ g [ 208 ].…”
Section: Extracellular Vesicles and Microgravitymentioning
confidence: 99%
“…Particularly, miR-383-5p was significantly increased, and aquaporin 4 (AQP4) decreased in the hippocampus. The authors suggest that bioinformatics could be used to map the crosstalk between the circulating metabolome and miRNAome to better to understand complex biological systems under µ g [ 208 ].…”
Section: Extracellular Vesicles and Microgravitymentioning
confidence: 99%
“…Moreover, the diabetic environment can lead to changes in exosome-miRNAs 28 , 29 . Moreover, cumulative studies have also confirmed that AQP4 is one of the key target genes of miRNAs 30 . Therefore, this review will be beneficial for elucidating the interorgan communication mechanism of glymphatic system function, regulation and providing a new strategy for the prevention and treatment of DCI.…”
Section: Introductionmentioning
confidence: 88%
“…Exosomal miRNAs, which can avoid degradation by RNase when released by donor cells, can be absorbed by the brain and regulate the expression of posttranscriptional genes 71 . Considering that the expression and localization of AQP4 on perivascular astrocyte endfeet is the main biomolecular basis of the glymphatic system, to further elaborate the hypothesis that peripheral tissue-derived exosomal miRNAs could induce AQP4 loss or redistribution, some of the miRNAs that target AQP4 are summarized in Table 2 30 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 . These miRNAs have multiple effects on DCI progression.…”
Section: Peripheral Tissue-derived Exosomal Mirnas Induce Aqp4 Loss O...mentioning
confidence: 99%
“…The Tail suspension manipulation was performed as Wronski described previously ( Wronski and Morey-Holton, 1987 ) with minor modifications as we used before ( Zhang et al, 2020 ). Six-month-old male mice were suspended by the tail attached to a chain hanging from a beam using a strip of adhesive surgical tape and maintained one per cage while they were tail-suspended.…”
Section: Methodsmentioning
confidence: 99%